Optimum duration of antithyroid drug treatment determined by assay of thyroid stimulating antibody in patients with Graves' disease. Issue 6670 (11th February 1989) - Edan, G.; Massart, C.; Hody, B.; Poirier, J. Y.; Lé Reun, M.; Hespel, J. P.; Leclech, G.; Simon, M.
Abstract : OBJECTIVE–To determine the optimal duration of antithyroid drug treatment by monitoring serum thyroid stimulating antibody values in patients with Graves' disease. DESIGN–Prospective longitudinal trial of patients with Graves' disease followed up for 24 months after withdrawal of treatment. SETTING–Tertiary referral centre. PATIENTS–A total of 64 consecutive patients with untreated Graves' disease, eight of whom were subsequently excluded. Fifty six patients completed the study. INTERVENTIONS–All patients were treated initially with carbimazole 40 mg, then with decreasing doses that maintained a euthyroid state. Treatment was scheduled to continue for 18 months but was withdrawn earlier if serum thyroid stimulating antibody became undetectable. END POINT–Serum values of thyroid stimulating antibody (assayed by stimulation of human thyroid cells in vitro) and thyroid hormones and thyroid state every three months during treatment and afterwards every six months for 24 months. MEASUREMENTS AND MAIN RESULTS–In 44 patients serum thyroid stimulating antibody became undetectable during treatment and treatment was withdrawn (median duration of treatment nine months, range 3-18 months). In 12 patients the antibody could be detected during 18 months of treatment. Among the first group of 44 patients initial values of the antibody before treatment were significantly lower than in the second group of 12 patients (median 225% (range 138-1236%) v 570% (250-1480%), p less than 0.001); the incidence of relapse was also lower (41% v 92%, p less than 0.001); and among those who did relapse the disease free interval after treatment was longer (median 12 months v 1 month, p less than 0.001). Moreover, the initial median serum values of thyroid stimulating antibodies were not related to the occurrence of relapse or remission as these did not differ between patients who did and did not have a relapse (median 267% (range 139-1480%) v 220% (range 138-1236%). CONCLUSION–Monitoring of serum thyroid stimulating antibody was a good guide to the duration of treatment as it allowed the treatment period to be considerably shortened in a large group of patients with no loss of efficiency.